(untitled) (Journal of Comparative Social Work, 2013)
The point of departure of this article is contemporary changes in the relationship between national and local decision making in the Norwegian political system. The last decades’ centralization tendencies seem to be challenged by a “new” emphasis on local discretion, and the article discusses how this will affect social work in municipalities. The changes are contested and controversial and allude to questions such as how much discretion should be given to local decision makers in the name of local democracy, and how much difference should be accepted in the name of diversity? The article argues that professional social work must be context-specific, meaning that in a wide sense local knowledge is a prerequisite for good social work. Devolution and local political and professional discretion are necessary in many cases, but not sufficient in themselves as conditions for success. Professional social workers will encounter a lot of difficult dilemmas arousing from issues related to the equality/liberty debate and the diversity/difference/equality debate in social work discourses. In order to approach these dilemmas, more of a focus on local deliberation and place shaping, in combination with a social work focus on democratic professionalism, is necessary. If this is done successfully, devolution and a recapturing of local discretion and decision-making power will empower clients as well as professionals. Thus, current changes in the relationship between different levels of decision making will enlarge the possibilities for professional social work in the municipalities.